Theology of Fleeing from Persecution - Miláčková, Věra; Veverková, Kamila (Church History Review, 2022)
This article ponders the theological reasoning behind fleeing from religious persecution. It emerged as a reaction to questions raised about the legitimacy and purpose behind the fleeing of Christians from the Middle East. We compared the types of fleeing and their underlying reasons mentioned in the Bible with stories of persecuted Christians fleeing from Iraq and Egypt, and we identified four different theological approaches – the ”Salvation at stake” approach, the Altruistic/common sense approach, the “Hearing God’s voice” approach, and an Opportunistic approach. Our aim is to provide an opportunity for the persecuted as well as those ministering to them to navigate among the different reasoning options the persecuted take when considering fleeing.